2020
DOI: 10.1039/d0sc01915a
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-catalysed C–F alumination of fluorobenzenes: mechanistic diversity and origin of selectivity

Abstract: A palladium pre-catalyst, [Pd(PCy3)2] is reported for the efficient and selective C–F alumination of fluorobenzenes with the aluminium(I) reagent [{(ArNCMe)2CH}Al] (1, Ar = 2,6-di-iso-propylphenyl). The catalytic protocol results in the...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 55 publications
2
21
0
Order By: Relevance
“…12 For our part, we have been interested in the development of L-type aluminylene ‡ ligands derived from low-valent aluminium(I) compounds and their role in the catalytic functionalisation of C-H, C-O and C-F bonds (Figure 1). [13][14][15] Despite rapid progress in this area, the fundamental properties of aluminium-based metalloligands remains poorly understood. A deeper, understanding of this interaction could improve insight into the existing catalytic processes, inspire new approaches to catalyst design and ultimately allow development of more sustainable catalysts based on 1 st row transition metals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 For our part, we have been interested in the development of L-type aluminylene ‡ ligands derived from low-valent aluminium(I) compounds and their role in the catalytic functionalisation of C-H, C-O and C-F bonds (Figure 1). [13][14][15] Despite rapid progress in this area, the fundamental properties of aluminium-based metalloligands remains poorly understood. A deeper, understanding of this interaction could improve insight into the existing catalytic processes, inspire new approaches to catalyst design and ultimately allow development of more sustainable catalysts based on 1 st row transition metals.…”
Section: Introductionmentioning
confidence: 99%
“…13,24,25 We have championed the catalytic applications of these types of complexes and suggested that dispersion interactions between the metalloligand and substrate can influence selectivity. 4,[13][14][15] In this paper, we report the synthesis of a series of eight new aluminylene complexes of 1 with first-row transition metals. These complexes have been characterised in the solid state and solution.…”
Section: Introductionmentioning
confidence: 99%
“…42 We proposed that ligand-assisted oxidative addition may be a key step during the reaction of 1 with fluorobenzene with the same catalyst system reported herein. 27 Ligand-assisted oxidative addition involves a fourmembered transition state (rather than a classical three-membered oxidative addition transition state)…”
Section: Resultsmentioning
confidence: 99%
“…This step has an impact on the scope and selectivity of the transformations as C-H bonds act as a transient directing group, being broken and remade along the reaction pathway (Scheme 6). 44,45 For example, the non-catalysed reaction of Al-2 with 2methylfuran at 80 C affords two isomers (Al-2c and Al-2d) of the ring-expanded metallacycle (Scheme 6a). The major species (Al-2d) results from insertion into the more hindered sp 2 C-O bond.…”
Section: C-h Aluminationmentioning
confidence: 99%
“…35 The same approach has been successfully applied on the C-O and C-F alumination of furans and uoroarenes respectively. 44,45 While a consistent mechanistic picture could be established for the alumination of sp 2 C-H bonds with Al-2, it remains unclear if and how palladium aluminylene intermediates are formed when using Al-1 as a stoichiometric reagent. 47 For example, one might imagine an elementary step that takes place in a similar but reverse fashion to the aforementioned double migration step from Pd/Al-5 (Scheme 8a).…”
Section: C-h Aluminationmentioning
confidence: 99%